2015
DOI: 10.3928/01477447-20150305-55
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Indications for Distal Tibial Epiphyseal Fractures in Children

Abstract: The goal of this study was to investigate the treatment methods and surgical indications of distal tibial epiphyseal fractures in children. Two hundred eighty-six children with distal tibial epiphyseal fractures were included in the study. Among these patients, 202 were male and 84 were female. Mean age was 11.7 years. A retrospective study on the postoperative long-term complications and related risk factors was performed. Treatment methods were determined according to the distance of fracture displacement. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
27
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 17 publications
3
27
0
1
Order By: Relevance
“…Most fractures included in our study were minimally displaced, suggesting that preoperative fracture displacement played an important role in the selection of FAPP vs. ORIF. In children the distance of fracture displacement is used as a selection criterion for choosing between closed and open reduction . In a recent study in 286 children, open reduction was selected in patients with >2 mm of fracture displacement, even after closed reduction .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most fractures included in our study were minimally displaced, suggesting that preoperative fracture displacement played an important role in the selection of FAPP vs. ORIF. In children the distance of fracture displacement is used as a selection criterion for choosing between closed and open reduction . In a recent study in 286 children, open reduction was selected in patients with >2 mm of fracture displacement, even after closed reduction .…”
Section: Discussionmentioning
confidence: 99%
“…In children the distance of fracture displacement is used as a selection criterion for choosing between closed and open reduction . In a recent study in 286 children, open reduction was selected in patients with >2 mm of fracture displacement, even after closed reduction . Based on our experience, we would recommend FAPP for fractures with minimal displacement.…”
Section: Discussionmentioning
confidence: 99%
“…The most common and important complication of distal tibia physeal fracture is PPC [21]. As shown in Table 3, the incidence of PPC ranges from 0.5 to 43% [2, 9, 16, 21, 2326]. The factors that contribute to the development of PPC are still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Özgür Çiçekli et al, Russo et al, and Leary et al found that PPC was significantly associated with the mechanism of injury [9, 23, 24], while Seel et al found no significant link between the mechanism of injury and PPC [25]. Leary et al demonstrated that the primary fracture displacement had a significant influence on PPC [24], but this was disapproved by other studies [2, 23, 25]. Many studies have confirmed that fibula fracture is an important risk factor for the development of PPC, which furthermore indicates that good anatomical reduction may reduce the rate of PPC [2, 16, 25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Ozljeda epifi zne ploče rasta (epifi zeoliza) jedan je od prijeloma koji nalažu posebnu kiruršku pozornost. 1,2 Epifi zeoliza distalne tibije druga je prema pojavnosti od svih epifi zeoliza i čini 15 -30% svih prijeloma u djece. 3,4 Važnost ove ozljede ogleda se, osim velike pojavnosti, i u neizvjesnom ishodu cijeljenja, unatoč pravilno provedenom postupku liječenja.…”
unclassified